Efficacy of ethnobotanical as anthelmintics in the productive performance of darag native chicken - Ozaraga, Ma. Sylvia I. (Passage Journal, 2014)
The study aimed to evaluate the efficacy of ethnobotanical such as opal-ipil, Betel nut, and papaya seeds as anthelmintics in the productive performance of native chicken. The study used 165 Darag native chickens subjected to a 3X3 factorial experiment in Randomized Complete Block Design (RCBD) with three replications. Two factors were considered: Factor A for the kind of ethnobotanical and Factor B for the dosages (2 g, 4 g, and 6 g/kg bw). Data on the efficacy of the ethnobotanical were obtained by through the percent reduction of roundworm egg per gram (EPG) count before and on the 7th, 14th, 21st, and 28th day post treatment. F-test and least significant difference (LSD), interpreted at 5% and 1% level of significance, were used for statistical analysis.